eterminants of seizure occurrence in preeclampsia before commencing and during treatment with magnesium sulphate - Imaralu, John O.; Badejoko, Olusegun O.; Loto, Olabisi M.; Ihongbe, John C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Eclampsia is considered as a consequence of severe preeclampsia, with magnesium sulphate regarded as gold standard in seizure treatment and prophylaxis. Convulsions have however been noted when criteria for severe preeclampsia were not met and in patients undergoing treatment with magnesium sulphate. Methods: A secondary analysis of data obtained from a prospective cross sectional study, involving assessment of clinical and biochemical markers of preeclampsia including magnesium in 75 patients with severe preeclampsia who were given magnesium sulphate using the Pritchard regimen. Results: Headache (p = 0.002), vomiting (p = 0.005) and prior occurrence of seizures before presentation (p = 0.001), were significant risk factors for occurrence of convulsions. In addition, serum magnesium levels were significantly lower (1.61±0.32 mg/dL) among patients who had seizures than in those who did not (2.01±0.25 mg/dL), (p<0.001). Systolic blood pressure (p = 0.22), diastolic blood pressure (p = 0.29), mean arterial blood pressure (p = 0.17) and proteinuria (p = 0.18) however did not determine the occurrence of seizures. Only 3/49 (6.1%) of the patients with severe hypertension (MAP≥125 mmHg) fitted, compared to 6/26 (23.1%) with mild hypertension (MAP<125mmHg) who convulsed (p = 0.04). Convulsion during treatment with MgS04 was associated with significantly lower levels of serum magnesium (4.04±0.5 mg/dL), than 4.63±0.5 mg/dL observed among patients with severe preeclampsia who did not convulse (p = 0.04). Conclusions: Headache, vomiting, prior convulsion and low serum magnesium levels preceded the occurrence of fits before treatment while, prior convulsion and low serum magnesium level consistently preceded the occurrence of fits during treatment of preeclampsia with magnesium sulphate.